2020
DOI: 10.1128/aac.01730-19
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Pharmacokinetics of Gentamicin between Oncology and Nononcology Pediatric Patients

Abstract: Dosing gentamicin in pediatric patients can be difficult due to its narrow therapeutic index. A significantly higher percentage of fat mass has been observed in children receiving oncology treatment than in those who are not. Differences in the pharmacokinetics of gentamicin between oncology and nononcology pediatric patients and individual dosage requirements were evaluated in this study, using normal fat mass (NFM) as a body size descriptor. Data from 423 oncology and 115 nononcology patients were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This study describes the differences in the PK of gentamicin, amikacin and vancomycin from premature neonates to adults using data from a large number of patients from different locations and different underlying medical conditions (Supporting Information Table S1). A previous study (data from sources 15 and 16 in this pooled analysis) 42 reported differences in the PK of gentamicin between oncology and non‐oncology paediatric patients by including NFM as a body size descriptor. NFM was applied 42 to describe the differences in the percentage of body fat between paediatric oncology (30.4%) and non‐oncology (14.9%).…”
Section: Discussionmentioning
confidence: 99%
“…This study describes the differences in the PK of gentamicin, amikacin and vancomycin from premature neonates to adults using data from a large number of patients from different locations and different underlying medical conditions (Supporting Information Table S1). A previous study (data from sources 15 and 16 in this pooled analysis) 42 reported differences in the PK of gentamicin between oncology and non‐oncology paediatric patients by including NFM as a body size descriptor. NFM was applied 42 to describe the differences in the percentage of body fat between paediatric oncology (30.4%) and non‐oncology (14.9%).…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to review the clinical pharmacokinetics and consequences for optimal dosing of gentamicin for infections caused by Gram-negative bacteria in various patient populations, focusing on new insights from the past decade. Several new PPK studies have focused on specific subpopulations including obese patients [46], critically ill patients [66,68,148], paediatric patients [90,92,106,149], neonates [112,[115][116][117][118]122], elderly patients [126] and patients on IHD [64,137], providing insights into the typical values of CL and V d in these patient groups, the variability of these parameters and possible explanations for this variability. But despite inclusion of covariates in many of these PPK models, unexplained IIV in CL and V d often remained high, especially in critically ill patients, resulting in wide ranges of C max , C min and AUC.…”
Section: Discussionmentioning
confidence: 99%
“…In infants, V d of gentamicin is estimated to be 0.35 L/kg [ 89 ], higher than reported in adults and lower compared with neonates [ 90 ]. Studies on pharmacokinetics of gentamicin in febrile neutropenic children aged 0–17 years showed a V d ranging from 0.25 L/kg to 0.32 L/kg [ 91 , 92 ].…”
Section: Pharmacokinetics In Paediatric Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum creatinine concentration was scaled by the expected sex‐ and age‐adjusted normal serum creatinine concentration as applied in other paediatric studies. 23 , 24 , 25 , 26 , 27 , 28 …”
Section: Methodsmentioning
confidence: 99%